2013
DOI: 10.1097/ppo.0b013e31829a68eb
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Phospholipids, EML4-ALK, and Hsp90 as Novel Targets in Lung Cancer Treatment

Abstract: Approximately one third of patients with non-small cell lung cancer have unresectable stage IIIA or stage IIIB disease; combined cytotoxic chemotherapy and radiation therapy delivered concurrently has been established as the standard treatment for such patients. Despite many clinical trials testing many different radiochemotherapy combinations, it seems that a plateau of efficiencies at the acceptable risk of complications has been reached. Clinical studies indicate that the improved efficacy of radiochemother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 126 publications
(168 reference statements)
0
7
0
Order By: Relevance
“…One classic example is the fusion gene BCR-ABL, which occurs in patients with CML, ALL and AML 11 . Notably, fusion genes can also serve as diagnostic markers and therapeutic targets, as shown for FGFR3-TACC3 fusions in glioblastoma and EML4-ALK fusions in lung cancer 12,13 . Although chromosomal rearrangements have been reported in EAC, no driver events caused by fusion genes have yet been described in this malignancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One classic example is the fusion gene BCR-ABL, which occurs in patients with CML, ALL and AML 11 . Notably, fusion genes can also serve as diagnostic markers and therapeutic targets, as shown for FGFR3-TACC3 fusions in glioblastoma and EML4-ALK fusions in lung cancer 12,13 . Although chromosomal rearrangements have been reported in EAC, no driver events caused by fusion genes have yet been described in this malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…11 Notably, fusion genes can also serve as diagnostic markers and therapeutic targets, as shown for fibroblast growth factor receptor 3 (FGFR3)-transforming acidic coiled-coil containing protein 3 (TACC3) fusions in glioblastoma and echinoderm microtubule-associated protein-like 4 (EML4)-anaplastic lymphoma kinase (ALK) fusions in lung cancer. 12,13 Although chromosomal rearrangements have been reported in EAC, no driver events caused by fusion genes have yet been described in this malignancy. Recently, Blum et al 14 identified ribosomal protein S6 kinase B1 (RPS6KB1)-vacuole membrane protein 1 (VMP1) as a fusion transcript that modulates autophagy in EAC.…”
Section: Introductionmentioning
confidence: 99%
“…The PUFA-containing lipids are mostly affected by the initial formation of phospholipid hydroperoxides and secondary lipid peroxidation products, such as thiobarbituric acid-reactive substances and 4-hydroxynonenal [58]. It has been proposed that phospholipase A 2 (PLA 2 ) is activated by oxidized phospholipids, and protects membranes from damage by peroxidation by preferentially cleaving the oxidatively modified species [59,60]. Indeed, PLA 2 is known to be activated by irradiation in order to repair the attacked phospholipids and generate lipid mediators contributing to survival.…”
Section: Discussionmentioning
confidence: 99%
“…Bufalin, a primary active ingredient of TCM Chan-Su , has the capacity of downregulating p-AKT and HSP27 and activating procaspase-3, procaspase-9, finally leading to cell apoptosis in pancreatic cancer [ 78 ]. HSPs, especially HSP90, are now confirmed to be essential for malignant transformation and progression [ 81 ]. In clinic, HSPs inhibition by TCMs might make the cancer cells more sensitive to chemotherapy.…”
Section: The Role Of Tcm-regulated Proteins In Cancer Therapymentioning
confidence: 99%